Informational Books for Children - Asri, Tri Mega (Record and Library Journal, 2016)
The ignorance of reading activity is a result of condition in which people are not accustomed to read because they are not familiar with the culture of writing. It is fueled by the entry of telecommunications technologies and broadcasting, especially children digital native generation. The ability to speak and communicate in children is very influential in the development of social interaction. Besides the language and communication skills are directly related to the process of thinking and developments in the search for solutions to problems in children. Informational books is one medium that can help the development of language and communication skills in children. Informational books can convey knowledge of all the things they want to know the child, about science, about everything that exists and happens around the child to see the writing in a language that has a characteristic and image. The method used is literature study and data collection techniques to conduct a study review of the relevant literature. Informational books children as a means of communication, various forms of media including books have a major influence in shaping attitudes and behavior ofÂ children. A wide variety of informational books that has developed its own current trend where its use on children in need of assistance